Construindo a padroeira: aproximações entre Igreja e Estado em Nossa Senhora da Conceição Aparecida - Miyahira, Fernando Tetsuo Venueza (2011)
In this monograph, we intend to study the devotion to Our Lady Aparecida and their interactions with Brazilian politics, as Church s key moments in the late nineteenth century and first half of the twentieth century. The study of essays, articles and works focused on Brazilian politics and history of the Church in Brazil have been essential to this research as the study of documents found in the "Clock Tower" of the Basilica of Our Lady Aparecida. We understand that at the end of the research, politics and religion could hold a very strong popular devotion in the Brazilian South Region. Certainly, we realize that these three forces could together build what is now the patron saint of Brazil, the Virgin Our Lady of Aparecida